Bucket-handle meniscal tears in children under the age of 10: a literature review - Canton, Gianluca; Maritan, Guido; Impellizzeri, Francesco; Formentin, Cristina; Murena, Luigi (Acta Biomedica Atenei Parmensis, 2021)
Background and aim of the work: Traumatic meniscal tears are raising in skeletally immature patients due to increasing participation in sport activities. Nonetheless, meniscal tears remain a rare injury in children, with a lack of evidence regarding treatment and outcome. The aim of the study is to review the literature on BHMT in children aged under 10 years. Methods: Two independent reviewers conducted a systematic search of Embase, Medline and Pubmed databases to report a summary of literature evidence about epidemiology, clinical presentation, diagnosis, treatment and outcome of BHMTs in children under the age of 10. Result: Eight articles have been considered, including seven case reports and one case series. We found 21 cases of BHMTs in children under 10 years. The injury occurred in the medial meniscus in 8 cases (66,7%), while in 4 cases (33,3%) on a lateral discoid meniscus. The mean reported age is 4,6 years (range 2 years - 9 years), with prevalence of the female sex (62,5%). Conclusion: BHMT is an uncommon lesion in children under 10 years old. It can be suspected after a history of knee trauma in patients with knee pain, effusion and locking. MRI is the best technique for the diagnosis. Current strategy of treatment is to preserve the meniscus through different arthroscopic suture techniques.